Two and Three-Dimensional Shoreline Behaviour at a MESO-MACROTIDAL Barred Beach - Angnuureng, D.B.; Almar, R.; Senechal, N.; Castelle, B.; Appeaning Addo, K.; Marieu, V.; Ranasinghe, R. (Journal of Coastal Conservation, 2017)
The present work investigates cross-shore shoreline migration as well as its alongshore variability (with deformation) on timescales of days to years using 6 years of time-averaged video images. The variability of the shoreline is estimated through empirical statistical methods with comprehensive reference to three scales of variability. At the meso-to macro-tidal barred Biscarrosse beach, shoreline responds in decreasing order at seasonal (winter/summer cycles, 52%), event (storms, 28%) and inter-annual scales. Whereas seasonal evolution is dominated by wave climate modulation, short-term evolution is influenced by tidal range and surf-zone sandbar characteristics. The influence of tide range and sandbars increases when timescale decreases. This is even more the case for the alongshore deformation of the shoreline which is dominated by short-term evolution. An EOF analysis reveals that the first mode of shoreline change time series is associated with cross-shore migration and explains 58% of the shoreline variability. The rest of the modes are associated to deformation which explain 42% of shoreline variability.
Keywords: Video Imagery; Shoreline Change; Event Scale; Seasonal Evolution; Sandbar; Tide; Biscarrosse Beach; Aquitaine Coast; EOF